Development of the late glacial Baltic basin and the succession of vegetation cover as revealed at Palaeolake Haljala, northern Estonia - Saarse, Leili; Niinemets, Eve; Amon, Leeli; Heinsalu, Atko; Veski, Siim; Sohar, Kadri (Estonian Journal of Earth Sciences, 2009)
The 4.5 m thick Haljala sequence in North Estonia was studied to provide information on palaeoenvironmental changes between 13 800 and 11 300 cal yr BP. Late glacial environmental history of North Estonia was reconstructed using AMS-dated pollen record, sediment composition, plant macrofossils, and ostracods. The obtained data show environmental fluctuations that are linked to the climate shifts of the Last Termination in the North Atlantic region. Decrease in the arboreal pollen accumulation rate around 13 700–13 600 and 13 300–13 100 cal yr BP refers to short deterioration of climate within the Allerød Interstadial and has been correlated with the cooling of the Greenland Interstadial GI-1c and GI-1b events, respectively. Between 13 100 and 12 850 cal yr BP the pollen accumulation rate of trees, shrubs, and herb as well as organic matter increased, indicating short-term climate amelioration and establishment of pine-birch woods. This change has been correlated with the GI-1a event. Climate deterioration during the Younger Dryas (GS-1) was inferred from the reduction of tree pollen and flourishing of cold-tolerant species, such as Artemisia, Chenopodiaceae, and Cyperaceae. New data show that ice cover of the Pandivere Upland started to perish already about 13 800 cal yr BP.